2021
DOI: 10.1016/j.puhe.2021.05.024
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 media fatigue: predictors of decreasing interest and avoidance of COVID-19–related news

Abstract: Objectives COVID-19-related news is important for adherence to public health measures. We examined predictors of interest and avoidance of COVID-19 news in Lithuania. Study design Online survey. Methods An online survey was conducted in between October and December 2020 targeting the general population in Lithuania. Participants rated their interest and avoidance of news about the COVID-19 pandemic, with possible answers ranging from ‘complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 22 publications
3
32
1
Order By: Relevance
“…As hypothesized, people who reported higher levels of pandemic fatigue were those with lower levels of concern, who perceived they are unlikely to be infected, who believed the disease was spreading slowly, who thought they would experience mild disease if infected, or those with depression. Although no causal inferences can be inferred here, other studies have found that less fear of COVID-19 predicted diminished interest in or avoidance of COVID-19 news [41], which is part of the pandemic fatigue definition. In addition, information avoidance predicted a reluctance to engage in COVID-19 preventive behaviors in China [43].…”
Section: Comparison With Prior Workcontrasting
confidence: 65%
See 1 more Smart Citation
“…As hypothesized, people who reported higher levels of pandemic fatigue were those with lower levels of concern, who perceived they are unlikely to be infected, who believed the disease was spreading slowly, who thought they would experience mild disease if infected, or those with depression. Although no causal inferences can be inferred here, other studies have found that less fear of COVID-19 predicted diminished interest in or avoidance of COVID-19 news [41], which is part of the pandemic fatigue definition. In addition, information avoidance predicted a reluctance to engage in COVID-19 preventive behaviors in China [43].…”
Section: Comparison With Prior Workcontrasting
confidence: 65%
“…As a result, they play a crucial role in the increase of incidence rates in several countries, such as in Spain during the summer of 2021 [40]. Younger age was also found to be associated with greater risk of decreasing or diminished interest and avoidance of news about COVID-19 [41]. Therefore, it is necessary to develop campaigns and information strategies specifically addressed to this group of population to overcome these difficulties.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…2 shows the proportion of articles per publication source. There is considerable variation in the distribution across sources, with the most articles coming from Yahoo Finance (92,605), MarketScreener (79,551), express.co.uk (44,942), Reuters (23,861), CNBC (20,968), MarketWatch (20,962), TheGuardian (18,953), CNN (17,006), The New York Times (13,784), The Conversation (5,352) and The Motley Fool (3,154). The remaining sources have a relatively low distribution of articles (< 2,500 each).…”
Section: Characteristics Of the Datasetmentioning
confidence: 99%
“…As agenda-setters, journalists fuel and respond to these information needs [4]. But in the case of COVID-19, news media's herd behavior cascaded in overreporting on the topic, such that the longer the pandemic lasted, the more people became "coronavirus-news-fatigued" [3,5]. Decisionmakers in organizations engage in issue management to cope with exogenous challenges such as those posed by the pandemic crisis.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 information avoidance among the elderly should therefore be taken seriously. However, previous studies on COVID-19 information avoidance has mainly focused on populations at large, college students, and consumers [ 14 , 27 , 28 , 29 , 30 , 31 ]. No studies, to the best of our knowledge, have been undertaken on COVID-19 information avoidance among elderly people.…”
Section: Introductionmentioning
confidence: 99%